Neonatal oxygen therapy in low- and middle-income countries: a pragmatic review - Jon Zelasko; Moshood O Omotayo; Sara K Berkelhamer; Susan Niermeyer; Lily Kak; Smita Kumar; Pavani K Ram (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background We assessed and summarized the peer-reviewed literature on the state of neonatal oxygen therapy in low and lower-middle income countries. # Methods A literature search was performed in 3 online databases (Pub Med, EMBASE, CAB Global Health) and amongst USAID's Service Provision Assessment (SPA) reports for publications pertaining to neonatal oxygen therapy in low and lower-middle income countries over the past 10 years (2007-2017). # Results Our search yielded 474 records, of which 26 were relevant and included in the review. Maintenance and indirect costs associated with the procurement of oxygen may constitute barriers to oxygen supply. The quality of therapy provided to neonates was affected by factors including a lack of necessary equipment at neonatal healthcare facilities and high indirect costs associated with the procurement of oxygen. Pulse oximeters used for monitoring of oxygen therapy were available in healthcare facilities, but there is scant data on the frequency of that monitoring. There are some hospitals that deliver neonatal oxygen therapy without any necessary monitoring equipment. Prevalence of retinopathy of prematurity among neonates with risk factors ranged from 11.9-47.2%, which is notably higher than published rates in neonates of similar gestational age being treated in high-income countries. # Conclusion There is a lack of data that provides direct estimates of availability of neonatal oxygen equipment and related clinical applications of oxygen therapy across health systems, particularly around the usage and availability of necessary monitoring equipment. Attention to the maintenance of oxygen and ancillary equipment for neonates and quality improvement initiatives to promote adherence to those guidelines can reduce the morbidity and mortality burden among neonates in low and lower-middle income countries.